The concept of Europe as a cultural identity - Shehu, Fatmir Mehdi (2015)
The long discussion on the formulation of “Europe and her identity,” from a political, economic, cultural or religious aspect, has, on one hand, paved the way for the unity of European nations, and created many misconceptions in the mind-set of both the élite and the masses, the developed and undeveloped nations, on the other. The worry about the absorption of core principles of one’s culture within European Community and the superiority of high culture (a subculture presented by the élite in the society within the European Community) towards popular culture or low culture (a subculture presented by the majority of the community within the European Community) have created numerous obstacles for the construction of the concept of Europe as a cultural identity, which is the thrust of the study in this paper. Cultural identity is very essential for European Community, as it persuades its people to have a sense of self and how to interact with each other. Also, it contributes to people’s overall wellbeing and brings them closer regardless of their differences. This paper attempts to enlighten the discussion on the concept of Europe as a cultural identity highlighting the major elements on which Europe’s culture identity stands. It discusses the origin of the concept of “Europe,” the emergence of European culture, European language, cultural identity, the European cultural identity, and the influence of Hellenic, Roman, Christian, and Scientific traditions on the construction of the European cultural identity. The descriptive and analytical methodologies are employed in this paper. The findings give insights to the reality of the unity of European nations under the banner of culture.